The relative effectiveness of three methods of performing experiments and submitting reports on the achievement of students in college physics laboratory course - Mateo, Elsa Tan (Animo Repository, 1987)
The main purpose of the study is to determine the relative effectiveness on students' achievement of the three methods of handling physics laboratory classes: namely, group performance and group reporting (Method A) group performance but individual reporting (Method B) and individual performance and individual reporting (Method C). Forty-eight Physics II (Mechanics & Heat) laboratory students were used as subjects of the study. The students were exposed to three different methods of performing experiments and submitting reports, namely: group performance and group reporting (Method A) group performance and individual reporting (Method B) and individual performance and individual reporting (Method C). An achievement test developed and validated by the researcher was administered before and after the treatment. Standardized tests were also given to measure mental ability, scientific attitude and science interest. Product moment correlation coefficient, t-test and ANCOVA were used to analyze the data with mental ability, scientific attitude and science interest as covariates of the study. This study revealed that students performed equally well in Physics laboratory under these three methods of handling physics laboratory classes. They also performed equally well in four levels of learning namely: (1) Knowledge of apparatus, (2) Knowledge of procedure, (c) Analysis of data, and (4) Problem solving. Students' achievement in physics laboratory is highly related to the four levels of learning. Students' manipulated skills are highly related to mental ability but not significantly related to scientific attitude and science interest while students' practical ability is highly related to mental ability and science interest but not with scientific attitude.